Prevalence of erectile dysfunction in men with cancer: a systematic review and meta‐analysis. Issue 5 (14th September 2022) - Xiao, Tao; Pizzol, Damiano; Grabovac, Igor; Ilie, Petre Cristian; Yang, Lin; Barnett, Yvonne; Parris, Christopher; McDermott, Daragh T; Veronese, Nicola; Kronbichler, Andreas; Trott, Mike; Soysal, Pinar; et al.
Abstract : Sexual health among male cancer survivors is becoming an increasingly important aspect of health care as the number of survivors increases. Here the authors analyse the impact of cancer treatment and cancer types on the prevalence of erectile dysfunction among these men.